2021
DOI: 10.1016/j.envres.2021.110826
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viruses in foods and their potential transmission through the diet: A review of the literature

Abstract: Respiratory viruses are the main agents causing respiratory tract diseases. Nowadays, coronaviruses – and specifically, SARS-CoV-1, MERS-CoV and SARS-CoV-2 – are the principal responsible for the major epidemic outbreaks of the 21st century. The major routes of transmission for respiratory viruses – including coronaviruses – are via direct and indirect contacts. However, transmission through contaminated foods has not been extensively assessed. The present paper was aimed at reviewing scientific data on the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…The surface stability of certain viruses (e.g., SARS-CoV-2, NoV, and HAV) has led to concerns of potential surface transmission throughout the food supply chain ( Bolton et al, 2013 ; González et al, 2021 ; Rajiuddin et al, 2020 ). In this study, the inactivation efficacies of selected disinfectants against surrogate MS2 on food contact surfaces were tested, to reinforce both personal and food hygiene principles during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…The surface stability of certain viruses (e.g., SARS-CoV-2, NoV, and HAV) has led to concerns of potential surface transmission throughout the food supply chain ( Bolton et al, 2013 ; González et al, 2021 ; Rajiuddin et al, 2020 ). In this study, the inactivation efficacies of selected disinfectants against surrogate MS2 on food contact surfaces were tested, to reinforce both personal and food hygiene principles during the COVID-19 pandemic.…”
Section: Resultsmentioning
confidence: 99%
“… Dargahi et al (2021) investigated the SARS CoV-2 virus in environmental surfaces, while Gomes-Passos et al (2021) made an exploratory assessment of the occurrence of SARS-CoV-2 in aerosols in hospital facilities and public spaces of a metropolitan center in Brazil. In turn, González et al (2021) carried out a review on respiratory viruses in foods and their potential transmission through the diet, whereas Gwenzi and Rzymski (2021) showed a perspective on Africa's subdued research response to COVID-19. On the other hand, Iyer et al (2021) presented a solid waste perspective regarding environmental survival of SARS-CoV-2, while Jadil and Ouzir (2021) made a multi-country comparison to explore the predictors of health-protective behavior during the COVID-19 pandemic.…”
Section: Comments On Papers Published In the Virtual Speciasll Issuementioning
confidence: 99%
“…van Doremalen et al ( 2020 ) showed that in experimental settings (under controlled relative humidity and temperature), SARS-CoV-2 can persist for up to 24 h on cardboard and up to 72 h on hard surfaces such as steel and plastics. There is research evidence that cold chain transportation in the frozen food industry may have caused a recurrence of COVID-19 cases in destination (González et al 2021 ; Liu et al 2020 ). In fact, there are also multiple outbreaks of COVID-19 virus linked to imported frozen fruit before (Rispens et al 2020 ; Saupe et al 2020 ).…”
Section: Covid-19 Transmission In Cold Food Supply Chainmentioning
confidence: 99%